Assessing the Socio-Economic Impact of Infrastructure Development on Local Communities: A Mixed-Methods Approach - Oyelana Shrestha; Oyelana Forsyth; Mujuranto Sihotang; Marsono Marsel Sihotang; Shin Walsham (Intitute of Computer Science (IOCS), 2022)
This study analyzes the impact of infrastructure development on the socio-economic aspects of local communities using a mixed approach that combines quantitative and qualitative analysis. The aim of the research was to explore the relationship between infrastructure development and its effect on the welfare of the local population. The main findings show that the impact of infrastructure development has various and complex dimensions. The results of the analysis show that the impact is multidimensional, covering economic aspects such as growth and new job opportunities, as well as social aspects such as changes in lifestyle and social interaction. This research also highlights that the impact of infrastructure can vary significantly between different regions, depending on the type of infrastructure built and local characteristics. In this context, accessibility is found to be a factor that strongly influences socio-economic impacts. Infrastructure that increases accessibility can contribute to economic growth and increase people's welfare. In addition, community participation in the planning and implementation stages of infrastructure projects has also proven to have an important role in influencing the impact felt